Alcohol consumption and mortality from coronary heart disease: An updated meta-analysis of cohort studies - Zhao, J.; Stockwell, Tim; Roemer, A.; Naimi, T.; Chikritzhs, T. (Alcohol Research Documentation, Inc Rutgers, 2017)
Objective: Previous meta-analyses estimate that low-volume alcohol consumption protects against coronary heart disease (CHD). Potential errors in studies include systematic misclassifica-tion of drinkers as abstainers, inadequate measurement, and selection bias across the life course. Method: Prospective studies of alcohol consumption and CHD mortality were identified in scholarly databases and reference lists. Studies were coded for potential abstainer biases and other study characteristics. The alcohol–CHD risk relationship was estimated in mixed models with controls for potential biases. Stratified analyses were performed based on variables identified as potential effect modifiers. Results: Fully adjusted meta-analysis of all 45 studies found significantly reduced CHD mortality for current low-volume drinkers (relative risk [RR] = 0.80, 95% CI [0.69, 0.93]) and all current drinkers (RR = 0.88, 95% CI [0.78, 0.99]). There was evidence of effect modification by cohort age, gender, ethnicity, and heart health at baseline. In stratified analyses, low-volume consumption was not significantly protective for cohorts ages 55 years or younger at baseline (RR = 0.95, 95% CI [0.75, 1.21]), for studies controlling for heart health (RR = 0.87, 95% CI [0.71, 1.06]), or for higher quality studies (RR = 0.86, 95% CI [0.68, 1.09]). In studies in which the mean age was 55 years or younger at baseline, there were significantly increased RRs for both former (RR = 1.45, 95% CI [1.08, 1.95]) and occasional drinkers (RR = 1.44, 95% CI [1.09, 1.89]) compared with abstainers. Conclusions: Pooled analysis of all identified studies suggested an association between alcohol use and reduced CHD risk. However, this association was not observed in studies of those age 55 years or younger at baseline, in higher quality studies, or in studies that controlled for heart health. The appearance of cardio-protection among older people may reflect systematic selection biases that accumulate over the life course.